2012
DOI: 10.1111/j.1467-8489.2012.00604.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of mining and smelting activities on property values: a study of Mount Isa city, Queensland, Australia

Abstract: Much publicity has been given to the problem of high levels of environmental contaminants, most notably high blood lead concentration levels among children in the city of Mount Isa because of mining and smelting activities. The health impacts from mining-related pollutants are now well documented. This includes published research being discussed in an editorial of the Medical Journal of Australia (see Munksgaard et al. 2010). On the other hand, negative impacts on property prices, although mentioned, have not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 43 publications
0
7
0
1
Order By: Relevance
“…However, our theoretical discussion and empirical evidence shown here implies that regional planners should be cautious of taking employment effects for granted. In addition, the employment and income growth outcomes are relevant for regional planning because beyond economic growth and prosperity, they are the source of several indirect local socio-economic consequences attached to mining booms/busts, as shown in the Australian case, such as migration and longdistance commuting (Measham et al 2013), housing issues (Haslam McKenzie and Rowley 2013;Neelawala et al 2013), income inequality changes (Kotey and Rolfe 2014;Fleming and Measham 2015b), crime, alcohol abuse and other related boomtown effects (Lawrie et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our theoretical discussion and empirical evidence shown here implies that regional planners should be cautious of taking employment effects for granted. In addition, the employment and income growth outcomes are relevant for regional planning because beyond economic growth and prosperity, they are the source of several indirect local socio-economic consequences attached to mining booms/busts, as shown in the Australian case, such as migration and longdistance commuting (Measham et al 2013), housing issues (Haslam McKenzie and Rowley 2013;Neelawala et al 2013), income inequality changes (Kotey and Rolfe 2014;Fleming and Measham 2015b), crime, alcohol abuse and other related boomtown effects (Lawrie et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This fact implies the potential existence of spatial autocorrelation of residuals terms, as well as potential spatial heterogeneity of any econometric specification. Both problems have been widely discussed in the spatial econometrics literature and different methods exist to control them (Anselin 1988;Neelawala et al 2013). On the other hand, it is also important to consider the heterogeneity of effects across regions as averaging results of effects across regions can produce misinterpretations of mining impacts.…”
Section: Some Empirical Challenges When Assessing Local Economic Impamentioning
confidence: 99%
“…However, various studies investigated the advantages and limitations of each functional form [39]. Nonetheless, there is no concrete evidence that one functional form is better than the other forms [71]. Henceforth, some researchers believe that the method of Box-Cox transformation allows investigators to choose the proper function of the hedonic regression model based on the best fit for a particular data set [78][79][80].…”
Section: The Hedonic Methods Model Developmentmentioning
confidence: 99%
“…Neelawala, Wilson, and Athukorala (2013) examined the effects of mining and smelting activities on nearby property values in Queensland, Australia [71]. The results revealed that properties located away from mining and smelting activities have a higher value, as compared to nearby properties.…”
Section: Hedonic Studies On Externalitiesmentioning
confidence: 99%
“…The hedonic pricing model is well established in the international economic literature (Rosen 1974;Freeman 2003 and Australian examples such as Fraser and Spencer 1998;Tapsuwan et al 2009;Hansen 2009;Hatton Space matters 39 MacDonald et al 2010;Neelawala et al 2012). Taylor (2008) provides an overview of equilibrium conditions where a hedonic price function relates the equilibrium market price of a house P h to its structural and lot characteristics S h , environmental amenity EA h , environmental dis-amenity ED h and neighbourhood attributes N h :…”
Section: Description Of the Modelmentioning
confidence: 99%